Valence-separated representation of reward prediction error in feedback-related negativity and positivity. Issue 3 (11th February 2015) - Bai, Yu; Katahira, Kentaro; Ohira, Hideki
<x xml:space="preserve">Abstract</x> Feedback-related negativity (FRN) is an event-related brain potential (ERP) component elicited by errors and negative outcomes. Previous studies proposed that FRN reflects the activity of a general error-processing system that incorporates reward prediction error (RPE). However, other studies reported inconsistent results on this issue – namely, that FRN only reflects the valence of feedback and that the magnitude of RPE is reflected by the other ERP component called P300. The present study focused on the relationship between the FRN amplitude and RPE. ERPs were recorded during a reversal learning task performed by the participants, and a computational model was used to estimate trial-by-trial RPEs, which we correlated with the ERPs. The results indicated that FRN and P300 reflected the magnitude of RPE in negative outcomes and positive outcomes, respectively. In addition, the correlation between RPE and the P300 amplitude was stronger than the correlation between RPE and the FRN amplitude. These differences in the correlation between ERP and RPE components may explain the inconsistent results reported by previous studies; the asymmetry in the correlations might make it difficult to detect the effect of the RPE magnitude on the FRN and makes it appear that the FRN only reflects the valence of feedback.